Answer:
Umar is 8 years old now.
Explanation:
Let the Umar's present age be x and his father's present age be y.
x + y = 46 ...... (sum of their ages)
y = 46 - x
Now since 3 years ago both of their ages would be reduced by three years therefore,
Three years ago Umar's age = (x - 3)
Three years ago his father's age = (y - 3)
According to question,
(y - 3) = 7 (x - 3)
Further solving,
y - 3 = 7x - 21
Now substituting the value of y,
(46 - x) - 3 = 7x - 21
43 - x = 7x - 21
7x + x = 43 + 21
8x = 64
x = 64/ x = 8 years
So the Umar's present age is 8 years.